Biomimetic nanoparticles for tumor immunotherapy - Yu, Hanqing; Wu, Meng; Chen, Siyu; Song, Mingming; Yue, Yulin (Frontiers in Bioengineering and Biotechnology, 2022)
Currently, tumor treatment research still focuses on the cancer cells themselves, but the fact that the immune system plays an important role in inhibiting tumor development cannot be ignored. The activation of the immune system depends on the difference between self and non-self. Unfortunately, cancer is characterized by genetic changes in the host cells that lead to uncontrolled cell proliferation and evade immune surveillance. Cancer immunotherapy aims to coordinate a patient's immune system to target, fight, and destroy cancer cells without destroying the normal cells. Nevertheless, antitumor immunity driven by the autoimmune system alone may be inadequate for treatment. The development of drug delivery systems (DDS) based on nanoparticles can not only promote immunotherapy but also improve the immunosuppressive tumor microenvironment (ITM), which provides promising strategies for cancer treatment. However, conventional nano drug delivery systems (NDDS) are subject to several limitations in clinical transformation, such as immunogenicity and the potential toxicity risks of the carrier materials, premature drug leakage at off-target sites during circulation and drug load content. In order to address these limitations, this paper reviews the trends and progress of biomimetic NDDS and discusses the applications of each biomimetic system in tumor immunotherapy. Furthermore, we review the various combination immunotherapies based on biomimetic NDDS and key considerations for clinical transformation.